Avaliação em idosos do seu conhecimento sobre prevenção de quedas e por variáveis associadas - Boa Sorte, Fabiano Cardoso (2021)
This study refers to the knowledge of the elderly in relation to the prevention of falls and how it can impact their lives, and at the beginning I show the inversion of the population pyramid and because of that, as the risks and events of falls that more recurrent to this population, becoming a growing public health problem. Then, simple measures are presented, which are easy to be adopted by the elderly and which are efficient in preventing domestic accidents. The objectives of this study are to identify the level of information of the elderly regarding the risk factors for falls, in addition to verifying whether the educational intervention increases knowledge about such risks. As a method, a qualitative and quantitative, transversal, prospective and analytical approach was carried out, which aimed to analyse the knowledge of the elderly about preventive care for falls, aiming to assess the knowledge of the elderly in relation to personal care in the prevention of falls, with two groups of elderly people over the age of 65 answering a questionnaire, and one group received an explanatory leaflet and clarifications in the first interview and another in the second interview. The results have a statistical difference in relation to the Student's t test, of p = 0.0382 favourable to the first group, a result that demonstrates the importance of knowledge and guidance. Given all this, it is concluded that the level of knowledge in relation to risks is important to avoid falls, as well as the educational intervention contributes to increase the perception of risk factors, preserving the health and quality of life of the elderly